Boosting Alkaline Hydrogen and Oxygen Evolution Kinetic Process of Tungsten Disulfide‐Based Heterostructures by Multi‐Site Engineering. Issue 1 (10th November 2021) - Zeng, Jinsong; Zhang, Long; Zhou, Qian; Liao, Liling; Qi, Ying; Zhou, Haiqing; Li, Dongyang; Cai, Fengming; Wang, Hui; Tang, Dongsheng; Yu, Fang
Abstract: Alkaline water electrolysis is an advanced technology for scalable H2 production using surplus electricity from intermittent energy sources, but it remains challenging for non‐noble electrocatalysts to split water into hydrogen and oxygen efficiently, especially for tungsten disulfide (WS2 )‐based catalysts. Density functional theory calculations in combination with experimental study are used to establish a multi‐site engineering strategy for developing robust WS2 ‐based hybrid electrocatalyst on mesoporous bimetallic nitride (Ni3 FeN) nanoarrays for bifunctional water splitting. This ingenious design endows the catalyst with numerous edge sites chemically bonded with the conductive scaffold, which are favorable for water dissociation and hydrogen adsorption. Benefiting from the synergistic advantages, the N‐WS2 /Ni3 FeN hybrid exhibits exceptional bifunctional properties for hydrogen and oxygen evolution reactions (HER and OER) in base with excellent large‐current durability, requiring 84 mV to afford 10 mA cm −2 for HER, and 240 mV at 100 mA cm −2 for OER, respectively. Assembling the catalytic materials as both the anode and cathode to construct an electrolyzer, it is actualized very good activities for overall water splitting with only 1.5 V to deliver 10 mA cm −2, outperforming the IrO2 (+) //Pt (−) coupled electrodes and many non‐noble bifunctional electrocatalysts thus far. This work provides a promising avenue for designing WS2 ‐based heterogeneous electrocatalysts for water electrolysis. Abstract : Density functional theory calculations in combination with experimental study are used to establish a multi‐site engineering strategy for developing robust WS2 ‐based hybrid electrocatalyst on mesoporous bimetallic nitride nanoarrays for bifunctional water splitting in base, requiring 84 mV to afford 10 mA cm −2 for hydrogen evolution reaction, and 240 mV at 100 mA cm −2 for oxygen evolution reaction with excellent large‐current durability.